2016
DOI: 10.1159/000443994
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive Effects of Alpha Lipoic Acid on Obesity-Related Cancers

Abstract: Background: It has been generally accepted that being overweight or obese is a risk factor for several types of cancers, including breast, thyroid, colon, pancreatic and liver. In fact, people who are obese have more fat tissues that can produce hormones, such as insulin or estrogen, which may cause cancer cells to grow. Alpha lipoic acid (ALA) is anorganosulfur compound derived from octanoic acid, which is produced in animals normally, and is essential for aerobic metabolism. Summary: Studies in both in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 76 publications
0
18
0
1
Order By: Relevance
“…Moreover, people with more fat tissue produce more hormones like insulin, and their cell proliferation is upregulated [51]. Alpha lipoic acid is an organosulfur compound and has anti-oxidative functions.…”
Section: Obesitymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, people with more fat tissue produce more hormones like insulin, and their cell proliferation is upregulated [51]. Alpha lipoic acid is an organosulfur compound and has anti-oxidative functions.…”
Section: Obesitymentioning
confidence: 99%
“…Alpha lipoic acid is an organosulfur compound and has anti-oxidative functions. Pre-treatment with Alpha lipoic acid reduces oxidant formation [51]. Matrix metalloproteases and glucose-induced adenosine triphosphate production are increased, uncoupling protein 2 mRNA and the consecutive protein expression is regulated and glucosestimulated insulin secretion is restored [51].…”
Section: Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…α‐Lipoic acid (LA) is an organosulphur compound derived from octanoic acid. Because of their unique characteristics to work both in hydrophilic and lipophilic environments, LA and its reduced form dihydrolipoic acid (DHLA) have gained considerable attention as biological thiol antioxidants, which are central to antioxidant defense in nervous system tissues …”
Section: Introductionmentioning
confidence: 99%
“…Because of their unique characteristics to work both in hydrophilic and lipophilic environments, LA and its reduced form dihydrolipoic acid (DHLA) have gained considerable attention as biological thiol antioxidants, which are central to antioxidant defense in nervous system tissues. [7][8][9][10] We have previously demonstrated that α-LA shows neuroprotective effects in various models of neurotrauma including SCI. [11][12][13] Based on our observations, we further hypothesized that decreasing neuronal degeneration with LA could be protective against neurogenic bladder induced by SCI, and could reverse the functional, structural, and biochemical alterations in the neurogenic bladder.…”
mentioning
confidence: 99%